Global economic crisis impact on organic food consumption in the Czech Republic - Majerova, Jana; Cizkova, Sarka (Frontiers in Sustainable Food Systems, 2024)
Introduction This study investigates the impact of the global economic crisis of 2008 on organic food consumption in the Czech Republic. The structure of this study includes general consumption attitudes and consumption of individual organic food items (organic milk). The goal of this study is to quantify the influence of selected income macroeconomic indicators on organic food consumption (in general and individually). This study is focused on analyzing how this impact changed after 2008 in both prospectives. Methods Methodologically, the error correction methodology (ECM) has been applied. However, it has been modified to incorporate breakpoint analysis to model the impact of the global economic crisis on organic food consumption. Thus, the total consumption of organic food and consumption of organic milk has been investigated. Results Econometric verification of the estimated model proved that there was a statistically significant positive dependence of both indicators of organic food consumption on all the investigated indicators of income before 2008. Nonetheless, it was also proved that this dependence disappeared after the global economic recession in 2008. This retrospective analysis provides a valuable view of the mechanisms of organic food consumption changes caused by economic crises. Discussion Prospective repetition of the research with the data from the current crisis could enrich the theory of organic food consumption. On the one hand, the results of hypotheses testing could be verified, and thus, the mechanisms of consumer reactions to the crisis could be identified, and the model of reaction to the next crisis cycle could be developed so as not to harm radically this sector. On the other hand, the results of hypothesis testing could be denied, and thus, the evolution in organic food perception and consumption could be stated. In this case, the need to revise the so-far formulated theoretical approaches would be proved.